Leadership Style and Educational Quality at State Islamic University - Evi Muafiah; Swasti Maharani; Nadhif Muhammad Mumtaz (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to identify the leadership style of Kyai in monitoring the quality of education at Ma'had Al-Jami'ah UIN Maulana Malik Ibrahim Malang, as well as the strategic steps of kiai in improving the quality of the Ma'had Al-Jami'ah institution. This research is qualitative research type using descriptive-analytic method. This research was conducted at Ma'hadal-Jami'ah UIN Malang. The primary sources are Kyai, Murabby, Musyrif, Mu'allim, and Mahasantri Ma'hadalJami'ah UIN Maliki Malang. And secondary sources are books, dissertations, theses, journals, articles, and other related sources. with research. Then the data collection technique uses document review, in-depth interviews, and observation. The results of this research concluded that the leadership style of kiai in Ma'had al-Jami'ah UIN Malang used the Transformasional leadership style. This can be seen from his charismatic figure and his capability for being a role model (uswah) in making any decisions (Idealized Influence), he also very inspiring and always motivating all the academic community of Ma’had al-Jami'ah (inspirational motivation), encouraging musyrif/ah, Murabbi/ah to always do innovation (Intellectual stimulation), He always listen any input and suggestions from the musyrif/ah, Murabbi ah (Individualized reason). This research emphasizes the study of kiai leadership in terms of maintaining the quality of education, This very differ with previous research which is only discuss about quality issues related to institutional transformasional leadership studies without the existence of central figure, which is researched by many scholars such as Ahmad Maki in his thesis under entitled "Leadership Transformasional in fostering tolerance”